Politik Etnisitas Dalam Upaya Pemekaran Provinsi Kotawaringin - Ricky Zulfauzan; Kris Nugroho; Dwi Widyatuti Budi (Institut Teknologi Sepuluh Nopember, 2019)
This study aims to provide a descriptive analysis of ethnicity politics from the perspective of Glazer and Moynihan